COMPARATIVE EFFICACY OF CONTINUOUS AEROBIC EXERCISE, MODERATE-INTENSITY INTERVAL TRAINING, AND HIGH-INTENSITY INTERVAL TRAINING IN ADULTS WITH CARDIOMETABOLIC AND PSYCHIATRIC RISK: A SYSTEMATIC REVIEW WITH EMPHASIS ON MENTAL HEALTH AND MUSCULOSKELETAL ADA - Dawid Wiczkowski; Mykola Sobchynskyi; Iga Kiełbaszewska; Dmytro Kowalczuk; Kamil Turlej; Darya Lazitskaya; Wiktoryia Kasianik; Valeryia Milasheuskaya; Katsiaryna Miraniuk; Andrzej Myrny; Monika Stepińska (International Journal of Innovative Technologies in Social Science, 2025)
Background and Aim: Aerobic exercise is a widely recommended non-pharmacological therapy for preventing and managing metabolic and cardiovascular diseases, as well as promoting psychological well-being. Interval training—especially high-intensity interval training (HIIT) and moderate-intensity interval training (mHIT)—has gained attention as a time-efficient alternative to moderate-intensity continuous training (MICT). Furthermore, emerging evidence indicates potential musculoskeletal adaptations that may influence adherence and performance, as well as the possibility of reducing medication dosage in certain psychiatric and hypertensive populations. This systematic review synthesizes global evidence comparing these exercise modalities in adults (≥18 years), focusing on cardiometabolic risk factors, mental health, and musculoskeletal responses.Methods: Following PRISMA guidelines, we searched PubMed, Web of Science, and Scopus (2008–2023) for randomized controlled trials (RCTs) and meta-analyses investigating MICT, mHIT, or HIIT in adults with or at risk for cardiometabolic or psychiatric conditions. Primary outcomes included blood lipids, insulin sensitivity, blood pressure, endothelial function, inflammatory markers, VO₂max, mental health parameters, and musculoskeletal adaptations. Secondary outcomes included potential changes in medication usage.Results: A total of 78 RCTs and 14 meta-analyses were included. Both MICT and interval training improved blood lipids, insulin sensitivity, and blood pressure significantly. HIIT was often associated with more pronounced or time-efficient gains in VO₂max and endothelial function. Regarding mental health, aerobic exercise (whether continuous or interval-based) consistently reduced depressive and anxiety symptoms, and several studies noted a possibility of tapering psychiatric medication in stable patients. Some evidence hinted that higher-intensity intervals might confer slightly larger acute mood benefits, though differences were modest. Preliminary reports also suggested that improvements in muscle strength and bone density markers could further optimize outcomes, especially in mHIT protocols.Conclusion: Regular aerobic exercise—whether delivered continuously or via intervals—confers significant benefits for cardiometabolic, musculoskeletal, and mental health outcomes in adults. HIIT may offer superior physiological benefits in less total exercise time, whereas MICT is widely accessible and well-tolerated. Future research should address long-term adherence, medication tapering in psychiatric and hypertensive populations, and the synergy between skeletal muscle adaptations and overall health.